2022
DOI: 10.1038/s41523-022-00475-1
|View full text |Cite
|
Sign up to set email alerts
|

MRI to assess response after neoadjuvant chemotherapy in breast cancer subtypes: a systematic review and meta-analysis

Abstract: This meta-analysis aimed to estimate and compare sensitivity, specificity, positive- (PPV) and negative predictive value (NPV) of magnetic resonance imaging (MRI) for predicting pathological complete remission (pCR) after neoadjuvant chemotherapy (NAC) in patients with early-stage breast cancer. We stratified for molecular subtype by immunohistochemistry (IHC) and explored the impact of other factors. Two researchers systematically searched PUBMED and EMBASE to select relevant studies and extract data. For met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In addition, it would be interesting to further analyze whether sNKG2DLs are useful for assessing the response to neoadjuvant therapy in breast cancer patients. To date, response assessment to neoadjuvant therapy in breast cancer is primarily performed using imaging modalities such as MRI, ultrasound, and mammography [55][56][57][58][59]; therefore, sNKG2DL levels in relation to neoadjuvant therapy may serve as a complementary, easyto-use, cost-effective, and non-invasive tool for response assessment that could benefit many patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it would be interesting to further analyze whether sNKG2DLs are useful for assessing the response to neoadjuvant therapy in breast cancer patients. To date, response assessment to neoadjuvant therapy in breast cancer is primarily performed using imaging modalities such as MRI, ultrasound, and mammography [55][56][57][58][59]; therefore, sNKG2DL levels in relation to neoadjuvant therapy may serve as a complementary, easyto-use, cost-effective, and non-invasive tool for response assessment that could benefit many patients.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have enough data to evaluate the relationship with TILs in the residual tumor to RFS, but work is underway to incorporate TILs in the residual tumor after NAC in the RCB to further stratify post-neoadjuvant prognosis(38).Since MRI is more accurate in evaluating response to NAC compared to mammography, ultrasound and physical examination, it is widely used in clinical practice (39)(40)(41). Radiological assessment alone is, however, not accurate enough to guide treatment decisions (42). A (semi-) automated method for evaluating response to NAC could be of interest, since manual measurement by RECIST is associated with intra-and interobserver variability (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, axillary LN response to NAC is rarely assessed by CT [11] . Furthermore, the results of the SENTINA and ACOSOG 1071 studies indicated that sentinel lymph node biopsy (SLNB) after NAC had a false negative rate of greater than 10 % for patients with unselected breast cancer [9] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%